Effect Of Knowledge Hiding Behavior on Employees' Passion: Field Study in a Sample of Electronic Payment Companies (Journal of Accounting and Financial Studies ( JAFS ), 2026)
This research aims to examine the impact of knowledge hiding behavior as an explanatory variable with its dimensions (evasive hiding, rationalized hiding, and playing dumb) on employee passion as a responsive variable with its dimensions (work enjoyment, self-motivation, and self-identity) in electronic payment companies. The research problem was identified through an attempt to answer the main question: To what extent does knowledge hiding behavior affect employee passion among employees of electronic payment companies? The researchers selected electronic payment companies operating in Baghdad Governorate as the field of the study. A set of hypotheses was formulated, the most important of which states that knowledge hiding behavior has no effect on employee passion in electronic payment companies. The researchers adopted the descriptive–analytical approach as a framework for describing and analyzing the data related to the study variables. The questionnaire was used as the main tool for data collection, in addition to field interviews as a supporting tool. The questionnaire was distributed to a group of employees working in electronic payment companies representing the study sample, with a total of 132 respondents. The questionnaire data were analyzed using several statistical software programs (SPSS V.24 and AMOS V.24) to test the validity and reliability of the research measures, as well as to conduct simple and multiple regression analyses to identify the direct effects among the study variables. The study reached several conclusions, the most significant of which is the presence of a significant negative effect of knowledge hiding behavior on employee passion. Based on these results, the researchers recommended the necessity of building an organizational environment that supports a culture of knowledge sharing and exchange among colleagues by providing employees with material or moral incentives to overcome their fears of losing knowledge. In addition, organizations should develop a formal code of conduct that clarifies acceptable and unacceptable behaviors within the workplace and ensures employees’ commitment to them.